2018
DOI: 10.1080/21645515.2018.1515447
|View full text |Cite
|
Sign up to set email alerts
|

Improving efficacy of cancer immunotherapy through targeting of macrophages

Abstract: T cell-based immunotherapies have revolutionized the treatment against cancer. But complete and long-lasting efficacy is only observed in a fraction of the patient population. One of the suspected causes is the inability of cytotoxic T cells, endowed with tumor killing ability, to reach their malignant targets. Using dynamic fluorescence imaging to study the dynamic of T cells in tumors from patients with lung cancer, we have recently demonstrated that macrophages trap the T lymphocytes, which are not longer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Previous studies have also demonstrated that stromal TAMs have long-lasting interactions with stromal T cells, 'trapping' them in the stroma and preventing them from gaining access to the tumour cells [49]. Our findings suggest that the therapeutic targeting of TAMs may be important in enabling CD8 + cells to access the tumour, further enhancing and synergising current immune checkpoint-based immunotherapy in ARID1A mutant patients [42][43][44][45][46][47][48][49][50]. Known synthetic-lethal targeting strategies associated with ARID1A deficiency, such as ATR inhibitors and/or PARP inhibitors , may also help prime the immune system and synergise the immune checkpoint blockade.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have also demonstrated that stromal TAMs have long-lasting interactions with stromal T cells, 'trapping' them in the stroma and preventing them from gaining access to the tumour cells [49]. Our findings suggest that the therapeutic targeting of TAMs may be important in enabling CD8 + cells to access the tumour, further enhancing and synergising current immune checkpoint-based immunotherapy in ARID1A mutant patients [42][43][44][45][46][47][48][49][50]. Known synthetic-lethal targeting strategies associated with ARID1A deficiency, such as ATR inhibitors and/or PARP inhibitors , may also help prime the immune system and synergise the immune checkpoint blockade.…”
Section: Discussionsupporting
confidence: 57%
“…Given the impact of myeloid cells on immunotherapy reported in the previous paragraphs, it seems reasonable to combine ICIs with drugs that target these subsets (3,5,7). A huge amount of preclinical data supports this hypothesis and the relevance of these combinations is also emerging in the clinic.…”
Section: Combination Strategies For Improving Ici Therapy By Targetinmentioning
confidence: 92%
“…Depending on the TME, these myeloid populations can adopt very different phenotypes with distinct impact on the anti-tumor immune response, angiogenesis and invasion. Many reviews have analyzed the influence of tumor-infiltrating myeloid cells on the prognosis of cancer patients ( 32 35 ) and the mechanisms of negative and positive regulation of the anti-tumor immune response ( 3 , 4 , 36 ). Although most findings come from murine tumors, some clinical data are emerging that link the presence of myeloid cells in the TME with the outcome of approved immune checkpoint therapies, as discussed later ( 6 8 ).…”
Section: Biomarkers In Ici Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggest that cytokines secreted by TAMs can induce anti-apoptotic, hyperproliferative and metastatic responses in lung cancer (9)(10)(11). TAMs can weaken the immunotherapy by impede T cells from reaching tumor cells (12). Targeting TAMs may treat as a possible therapeutic strategy to improve T cell interaction with cancer cells, thereby shifting "immuneexcluded" tumors, which are refractory to immune checkpoint inhibitors, into tumors that respond to anti-PD-1 antibodies (12).…”
Section: Introductionmentioning
confidence: 99%